DYNAMICS OF INDICATORS OF PHYSICAL FITNESS AND ECONOMY AS A FACTOR OF SPORTS RESULTS OF HIGH-CLASS BIATHLONISTS - Myakinchenko, P.E.; Adodin, A.V.; Myakinchenko, E.B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study the dynamics of indicators of physical fitness and economy in the context of differences in the characteristics of the competitive activity of high-class biathletes. Methods and structure of the study. Four men and four women in "successful" and "unsuccessful" seasons according to the rating criterion in the World Cup studied the values and dynamics of 34 functional and motor indicators obtained from May to November of the preparatory period, as well as the dynamics of distance speed, last lap speed and accuracy shooting while standing during the competitive period. Results and conclusions. In addition to the well-known ones, another criterion for the effectiveness of the training process has been identified: "the dynamics of the functional and motor abilities of athletes in the preparatory period." For most indicators, the dynamics should be linear or exponentially increasing. The difference and dynamics of the result in the competitive period is largely determined by the distance speed.